Interferon-Gamma-Mediated Osteoimmunology - Tang, Mengjia; Tian, Li; Luo, Guojing; Yu, Xijie (Frontiers in Immunology, 2018)
Abstract: Osteoimmunology is the interdiscipline that focuses on the relationship between the skeletal and immune systems. They are interconnected by shared signal pathways and cytokines interconnect. Interferon-gamma (IFN-γ) plays important roles in immune responses and bone metabolism. IFN-γ enhances macrophage activation and antigen presentation. It regulates antiviral and antibacterial immunity as well as signal transduction. IFN-γ can promote osteoblast differentiation and inhibit bone marrow adipocyte formation. IFN-γ plays dual role in osteoclasts depending on its stage. Furthermore, IFN-γ is an important pathogenetic factor in some immune-mediated bone diseases including rheumatoid arthritis, postmenopausal osteoporosis and acquired immunodeficiency syndrome. This review will discuss the contradictory findings of IFN-γ in osteoimmunology and its clinical application potential.